Family Entrepreneurship in the Local Economic Structure: A Study in Ecuador - Ayaviri-Nina, Victor Dante; Zuniga Robalino, Allison Mishell; Romero-Flores, Martha Lucía; Condori, Daniela Guzman; Menar, Braulio Ramos (European Scientific Journal, ESJ, 2025)
This research paper analyzes the impact of family entrepreneurship on the economic structure of Ecuador, Guano Canton. It adopts a qualitative and quantitative approach. The sample represents the total entrepreneurial population, which includes 72 entrepreneurs. Using analytical methods such as multinomial logistic regression and multiple linear regression, it examines how family entrepreneurship, measured through income generated, entrepreneur training, and participation in fairs, relates to the canton's economic structure. It highlights the role of entrepreneurship in job creation, economic diversification, and social progress in the canton. It also emphasizes the dynamic interaction between entrepreneurs and the community, as well as the importance of training mechanisms and participation in fairs in promoting innovation and entrepreneurial development.